The Relationship Of Self-Concept And Lifestyle Of Students Receiving Bidikmisi Scholarship - Syifa Ulfah; Zadrian Ardi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
This study aims to describe self-concept, lifestyle, and examine the relationship of self-concept to the lifestyle of BIDIKMISI scholarship recipients.This research is descriptive and correlational research.The study population was students receiving BIDIKMISI scholarships majoring in UNP's BK FIP 2016-2019. The number of samples was 90 students who were obtained by using the Stratified Random Sampling technique. The instrument used was a questionnaire with a Likert scale model. The data obtained were analyzed using the percentage technique and Pearson product moment correlation with the SPSS program version 23.00.The results showed that in general the self-concept of BIDIKMISI scholarship recipients in the category was not positive and the lifestyle of scholarship recipients in the medium category, and there is a significant negative relationship between self-concept and the lifestyle of BIDIKMISI scholarship recipients.